An exploratory study of the concept of styling - Erestain, April Joy Jalmasco
ABSTRACT The study is a qualitative research that aimed to investigate the concept of 'styling' as employed in residential and contract design and examine its implications on the local profession of interior design. Semi-structured interviews were employed to gather the different perspectives regarding the concept of styling. Ten (10) informants composed of six (6) interior designers and (4) non-interior designers were selected through purposive sampling. Two sets of interview guides and a voice recorder were the instruments used in the study. Results showed that interior designers and non-interior designers defined the practice of interior styling in relation to aesthetics, editorial, retail design, placement of accessories, and design. It was mainly used in connection to aesthetics. Using the data as basis, styling can therefore be characterized as creating pleasing residential or commercial interiors through the placement and addition of accessories and soft furnishings. This was commonly seen in interior settings for visual merchandising, and set ups for photo shoots. Based on the data, interior styling, decorating, and designing were not comparable to each other and were different in terms of scope, time element, focus, and purpose. However, findings showed that interior styling was the last part of interior design wherein accessorizing happens. Thus, stylists need to have a degree and a license in interior design to practice interior styling. Additionally, the study concludes that interior styling can provide new opportunities to interior designers but it can also pose as a potential threat to the profession in the near future.